A Coronal Mass Ejection Impacting Parker Solar Probe at 14 Solar Radii - Carlos R. Braga; Vamsee Krishna Jagarlamudi; Angelos Vourlidas; Guillermo Stenborg; Teresa Nieves-Chinchilla (The Astrophysical Journal, 2024)
The relationship between CME properties in the corona and their interplanetary counterparts is not well understood. Until recently, a wide spatial gap existed between the two regions, which prevented us from disentangling the spatial and temporal evolution of CMEs. NASA’s Parker Solar Probe (PSP) has imaged multiple CMEs since its launch in 2018, but these events either intercepted the spacecraft far from the corona or completely missed it. Here we describe one of the first CMEs observed simultaneously by remote sensing and in situ instruments, and compare the corresponding measured properties, such as orientation, cross section diameter, density, and speed. The CME encounter occurred on 2022 June 2, while PSP was around 14 solar radii from the Sun center. We reconstruct the CME with forward modeling and determine its morphology and kinematics. The reconstruction suggests that PSP misses the CME apex but encounters its flank. The encounter time matches the period when the PSP in situ measurements indicate the passage of a CME. We also reconstruct the flux rope diameter and orientation using the in situ magnetic field measurements. The results are consistent with the CME reconstruction from imaging data. The close agreement between remote sensing and in situ analyses suggests that discrepancies found in past studies are more likely associated with the CME temporal evolution. We also find that the magnetic field of the CME flank extrapolated to 1 au is well below the average solar wind background and likely indistinguishable from it. This point could explain past events where the CMEs' interplanetary counterparts were not identified.